2020
DOI: 10.1093/bib/bbz159
|View full text |Cite
|
Sign up to set email alerts
|

NCMCMDA: miRNA–disease association prediction through neighborhood constraint matrix completion

Abstract: Emerging evidence shows that microRNAs (miRNAs) play a critical role in diverse fundamental and important biological processes associated with human diseases. Inferring potential disease related miRNAs and employing them as the biomarkers or drug targets could contribute to the prevention, diagnosis and treatment of complex human diseases. In view of that traditional biological experiments cost much time and resources, computational models would serve as complementary means to uncover potential miRNA–disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(77 citation statements)
references
References 55 publications
0
77
0
Order By: Relevance
“…Emerging evidence has shown that non-coding RNA biomarkers play important roles in various human diseases including seminoma [ 40 ]. With the rapid development of computational prediction models, Chen et al proposed several innovative prediction models to identify non-coding RNA biomarkers correlated with human diseases [ 41 44 ]. Future studies will attempt to find significant non-coding RNA biomarkers of seminoma and may take advantage of these state-of-the-art computational models.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown that non-coding RNA biomarkers play important roles in various human diseases including seminoma [ 40 ]. With the rapid development of computational prediction models, Chen et al proposed several innovative prediction models to identify non-coding RNA biomarkers correlated with human diseases [ 41 44 ]. Future studies will attempt to find significant non-coding RNA biomarkers of seminoma and may take advantage of these state-of-the-art computational models.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most fundamental goals in biomedical research is to understand the molecular, physiological and pathological mechanisms underlying complex human diseases [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al (2019) made full use of the miRNA functional similarity, the disease semantic similarity, and a dual Laplacian regularization term to work for the matrix completion of miRNA-disease associations. Chen et al (2020) proposed a new computational model (NCMCMDA) that innovatively integrated neighborhood constraint with matrix completion to find out the absent miRNA-disease associations. Even though all of the above methods only needed experimentally validated miRNA-disease associations to make prediction with a good prediction effect, the optimal parameters selection still cannot be solved very well.…”
Section: Introductionmentioning
confidence: 99%